“Komunikasi Politik Capres Anies Baswedan Menuju Pemilu 2024 Melalui Media Sosial Instagram” - Ibnu Azka; Iswandi Syahputra (Jurnal Ilmu Komunikasi (J-IKA), 2023)
This article aims to discuss Anies Rasyid Baswedan's political communication through his Instagram social media. Political communication is one part of political activity which has the aim of conveying messages that are political in nature and carried out by politicians to political targets. Social media is now the stage for personal branding, which doesn't only belong to artists. But it is also important for anyone who will or has become a public figure. Although branding is usually used in product or service marketing, branding in the current millennial era is needed by anyone who has an interest in getting public attention, one of which is political actors, to portray themselves as an ideal leader. The research method used is descriptive qualitative by trying to understand a phenomenon on social media and trying to describe and analyze the findings of the data. This paper wants to answer the following questions. First, how Anies branded himself through social media Instagram. Second, What are the success factors for Anies' personal branding in utilizing Instagram social media. Third, what image will Anies build to the public as a candidate for the upcoming 2024 President.